2021
DOI: 10.3389/fnins.2021.790943
|View full text |Cite
|
Sign up to set email alerts
|

How Is the Norepinephrine System Involved in the Antiepileptic Effects of Vagus Nerve Stimulation?

Abstract: Vagus Nerve Stimulation (VNS) is an adjunctive treatment for patients suffering from inoperable drug-resistant epilepsy. Although a complete understanding of the mediators involved in the antiepileptic effects of VNS and their complex interactions is lacking, VNS is known to trigger the release of neurotransmitters that have seizure-suppressing effects. In particular, norepinephrine (NE) is a neurotransmitter that has been associated with the clinical effects of VNS by preventing seizure development and by ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 121 publications
(218 reference statements)
0
17
0
Order By: Relevance
“…A strong positive correlation was found between the noradrenergic and antiseizure effects of VNS. 48 Blockade of hippocampal α(2)receptors reversed the seizure-suppressing effect of VNS. 49 Other neurotransmitters such as GABA, glycine, and various amino-acid pools were found to be modified by VNS in the brain.…”
Section: Vns Therapy and Neurotransmitter And Cytokines Releasementioning
confidence: 99%
“…A strong positive correlation was found between the noradrenergic and antiseizure effects of VNS. 48 Blockade of hippocampal α(2)receptors reversed the seizure-suppressing effect of VNS. 49 Other neurotransmitters such as GABA, glycine, and various amino-acid pools were found to be modified by VNS in the brain.…”
Section: Vns Therapy and Neurotransmitter And Cytokines Releasementioning
confidence: 99%
“…With the current pharmaceutical technology, the treatment of epilepsy diseases mainly relies on medication, but patients can become somewhat dependent on medication. Vagus Nerve Stimulation (VNS) is a therapy option for patients with drug-resistant epilepsy who cannot get treatment [ 8 ]. Several researches conducted over the last few decades suggest that administering cannabinoids and activating the endocannabinoid system (ECS) are treatment methods for controlling epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with intractable focal epilepsy, surgical excision of the epileptogenic tissue is a well-established treatment option [7] With the current pharmaceutical technology, the treatment of epilepsy diseases mainly relies on medication, but patients can become somewhat dependent on medication. Vagus Nerve Stimulation (VNS) is a therapy option for patients with drug-resistant epilepsy who cannot get treatment [8]. Several researches conducted over the last few decades suggest that administering cannabinoids and activating the endocannabinoid system (ECS) are treatment Hindawi Computational and Mathematical Methods in Medicine Volume 2022, Article ID 3654181, 6 pages https://doi.org/10.1155/2022/3654181 methods for controlling epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the early tauopathy of the LC that appears to contribute to AD (Jacobs et al, 2021), synucleinopathy contributing to LC degeneration was also detected in prodromal dementia of Lewis bodies (Hansen, 2021). Finally, concerning existing therapies targeting the LC-NE system, it was suggested that the functional integrity of this system may be linked to responsiveness to Vagus Nerve Stimulation in patients with inoperable drug-resistant epilepsy (Berger et al, 2021; de Taeye et al, 2014; Hödl et al, 2020). In the context of healthy aging, our results indicate that, while LC contrast changes with age, LC responsiveness may remain stable such that any abnormal response may constitute an early sign of an unhealthy trajectory.…”
Section: Discussionmentioning
confidence: 99%